EPICAUTA ERYTHROCEPHALA (PALLAS, 1781) ТУРИНИНГ ЖАНУБИЙ ОРОЛБЎЙИДА ТАРҚАЛИШИ ВА БИОЭКОЛОГИК ҲУСУСИЯТЛАРИ - Сейлханова, А.Н.; Тилепов, Ж.; Калимбетова, Р.; Медетов, М.Ж. (SCIENCE and SOCIETY, 2022)
This article discusses the distribution of Epicauta erythrocephala in the natural and anthropogenic zones of the Southern Aral Sea, bioecological features and the benefits of Epicauta erythrocephala species in the larval stage of grasshopper cells by parasitizing on grasshopper cells, and also mentions the damage to agriculture by feeding on plants in the adult stage.
Keywords: butterdish; species Epicauta erythrocephala; region; agrocenosis; South Prearalie; pest; adult; development